Indicators of social and demographic processes in assessing quality of life for Almaty region (Journal of Geography and Environmental Management, 2019)
In this article considers the basic socio-demographic indicators of the quality of life in the Almaty region. The mainindicators of the quality of social considered: demographic indicators of fertility and mortality, life expectancy of thepopulation, the incidence of the population, the level of education.